The Potential Advantages of Tai Chi Chuan in Promoting Inhibitory Control and Spontaneous Neural Activity in Young Adults - Shen, Qi-Qi; Yin, Heng-Chan; Cui, Lei; Zhang, Jing-Yi; Wang, Dong-Ling; Zhu, Li-Na; Wang, Yuan; Li, Xiu-Juan (Frontiers in Behavioral Neuroscience, 2021)
Tai Chi Chuan is assumed to exert beneficial effects on brain functional activity and cognitive function in elders. Until now, empirical evidence of Tai Chi Chuan induced intra-regional spontaneous activity and inhibition control is not conclusive, whether this effect is better than that of other aerobic exercises is still unknown, and the role of Tai Chi Chuan in younger adults is not fully understood. Here we used resting-state functional MRI to investigate the effects of 8-week Tai Chi Chuan (n=12) and brisk walking (n=12) on inhibition control and fractional amplitude of low-frequency fluctuations (fALFF). The results found that Tai Chi Chuan had significant effects on inhibition control performance and spontaneous neural activity that were associated with significantly increased fALFF in the left medial superior frontal gyrus (Cohen's d=1.533) and the right fusiform gyrus (Cohen's d=1.436) and decreased fALFF in the right dorsolateral superior frontal gyrus (Cohen's d=1.405) and the right paracentral lobule (Cohen's d=1.132). Tai Chi Chuan had stronger effects on spontaneous neural activity than the brisk walking condition that was embodied in significantly increased fALFF in the left medial superior frontal gyrus (Cohen's d=0.862). There was a significant positive correlation between the increase in fALFF in the left medial superior frontal gyrus and the enhancement in inhibition control performance. The change in fALFF in the left medial superior frontal gyrus was able to explain the change inhibition control performance induced by Tai Chi Chuan. The results showed that (1) 8 weeks of Tai Chi Chuan intervention can improve processing efficiency related to inhibition control and alter spontaneous neural activity in young adults. (2) Tai Chi Chuan has advantages over brisk walking for optimizing spontaneous neural activity.